A Review of Dietary Ziziphus jujuba Fruit (Jujube): Developing Health Food Supplements for Brain Protection. (7th June 2017) - Chen, Jianping; Liu, Xiaoyan; Li, Zhonggui; Qi, Airong; Yao, Ping; Zhou, Zhongyu; Dong, Tina T. X.; Tsim, Karl W. K.
Abstract : The fruits of Ziziphus jujuba, known as jujube or Chinese date, are being consumed all around the world because of their health benefits, as both food and herbal medicine. Traditionally, one of the main functions of jujube, as described in herbal medicine, is to benefit our brain by calming down the mind and improving quality of sleep. Here, the activities of jujubes on nervous system are summarized and discussed. Jujube possesses neuroprotective activities, including protecting neuronal cells against neurotoxin stress, stimulating neuronal differentiation, increasing expression of neurotrophic factors, and promoting memory and learning. Flavonoid, cAMP, and jujuboside could be the potential bioactive ingredients to account for the aforesaid biological activities. These findings imply that jujube is a potential candidate for development of health supplements for prevention and/or treatment of neurological diseases.